2006
DOI: 10.1007/s11136-006-0031-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the health-related quality of life in patients with diabetic foot ulcers, with a diabetes group and a nondiabetes group from the general population

Abstract: Diabetic foot ulcer patients had much worse HRQL compared with the diabetes population and the general population, especially in physical health. Foot ulcer patients were more often men living alone, and obesity was a problem in both the foot ulcer patients and the diabetes population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
147
4
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(179 citation statements)
references
References 41 publications
25
147
4
3
Order By: Relevance
“…Amputations from complications related to DM place an individual at risk for additional amputation and have a 5 year mortality rate of 39% to 68% (Morris et al, 1998). People with diabetic foot ulcers have a lower health-related quality of life than the general population and diabetics without foot ulcers as well (Ribu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Amputations from complications related to DM place an individual at risk for additional amputation and have a 5 year mortality rate of 39% to 68% (Morris et al, 1998). People with diabetic foot ulcers have a lower health-related quality of life than the general population and diabetics without foot ulcers as well (Ribu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Majority of cases in present study were illiterate, belong to lower socio-economic class, and belonging to rural areas and were smokers/tobacco chewers/alcoholic, a comparable data on these aspects were not available in the literature. However, Ribu et al 5 In their study observed that greatest difference between diabetic foot ulcer patients and general population (as control) were more of the foot ulcer patients were men, older, living alone, less well educated and not working.…”
Section: Discussionmentioning
confidence: 89%
“…Obesity in these patients which significantly impaired mobility and work capacity is also associated with impaired HRQL. Ribu et al 5 also observed that the patients of diabetic foot ulcers reported significantly poorer Health Related Quality-of-Life (HRQL) than diabetic population, moreover, these patients had significant lower HRQL than the general population on all scales. In patients of leg ulcers, reduction of swelling, pain and/or discharge may be important in improving quality-of-life.…”
Section: Discussionmentioning
confidence: 96%
“…22,23 It is increasingly evident that not only a cure for the current worldwide diabetes epidemic is essential, but also for its major complications, affecting both small and large blood vessels. These complications occur in the majority of individuals with both type 1 and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%